KAJIAN KRITIS HUKUM PERTANAHAN DALAM PERSPEKTIF FIKIH - Nur, Iffatin (IAIN Tulungagung, 2014)
Conflicts of land had happened long time ago and commonlyinvolved ulama to mediate the conflict. This fact led to thedevelopment of the science of Islamic law (Fikih). As a science,fikih is expected to provide theoretical basis for solving problemsrelated to land ownership. Besides, it also provides theologicalbasis to help solving problems of land from the perspective ofreligion.Kata kunci: Hukum Pertanahan, Fikih